The marketing of high technology, with specific reference to marketing strategy dynamics of industrial electronics manufacturing in the Republic of South Africa - Struwig, Amori (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Com.) -- University of Stellenbosch, 1989.